Clinical Presentation And Management Of Central Neurocytoma In Pediatric Age Group - Narang, Arushi; Tambolkar, Sampada; Gawhale, Siddhi; Chavan, Devika; Mane, Shailaja (Journal of Neonatal Surgery, 2025)
Central neurocytoma is a rare, typically benign intraventricular tumor primarily affecting young adults, but its occurrence in the pediatric population is exceptionally uncommon. This case report aims to highlight the clinical presentation, radiologic features, surgical management, and the outcome of a pediatric central neurocytoma. Herewith, we report the case of a toddler who presented with signs of raised intracranial pressure. Magnetic resource imaging (MRI) brain revealed heterogenous soft tissue showing enhancement in right lateral ventricle lesion extending into third ventricle and aqueduct of Sylvius leading to resultant obstructive hydrocephalus. Patient underwent endoscopic septostomy with maximal safe resection and was diagnosed with Central Neurocytoma (WHO Grade 2) based on immunohistochemistry (IHC) analysis of intraoperative tissue sample. Despite the rarity of central neurocytomas in children, early diagnosis and appropriate management can lead to excellent long-term prognosis, emphasizing the importance of awareness among clinicians of this entity.